Analysis Busines of Iodized salt SMEs in Cirebon District - Hamid, Amellia Adani; Aldianto, Leo (Journal of Business and Management, 2014)
Cirebon Regency is the largest potential area in West Java to producing salt that attracts high interest of Small Medium Enterprise (SME). But unfortunately there are still a lot of iodized salt SMEs in Cirebon Regency experiencing difficulties in running the business. This research aim to identifying the main problems that may face by those SMEs, then will analyze by using theories of business and management in general perspective in order to provide alternative solutions and recommendations that can help developing the SMEs. This research use interview and observation as methods of primary data gathering. Interview and observation focus on 4 iodized salt SMEs in Cirebon Regency that each of them come from several villages and districts. These SMEs are expected represent the iodized salt SMEs in Cirebon Regency overall. From the results of data collection, researchers determined there are 5 common problems as follows: (1) difficulties in marketing the product, (2) difficulty in recruiting and attract employees to work with (3) no standard operating procedures that are held in the use of methods and technologies of producing iodized salt, (4) difficulty in getting supplies of iodine (5) and SNI certificate is considered expensive by most SMEs. The result analysis shows that iodized salt SMEs have uses methods and technologies according to the standard required from Indonesia Ministry of industry, the largest market demand for iodized salt are come from traditional market, grocery, and packaging market, while the scarcity of iodized content can be got alternatively by import from GAIN-UNICEF recommendation. Responding to the expensive cost of SNI problem, researcher doing financial analysis to calculate the investment analysis of the SNI certificate registration by taking sample 2 respondents of the 4 SMEs, the result obtained that each of them has NPV>0 it means their business which including the cost of SNI still deserve to be ran and developed even the payback period can be gained in the first year.Keyword: Iodized Salt SMEs, Cirebon Regency, Iodine, Marketing Strategies, Investment Analysis, Methods and Technologies, Compensation